Machinability Performance of Single Coated and Multicoated Carbide Tools During Turning Ti6Al4V Alloy - Ali, Ahsen; Younas, Muhammad; Khan, Mushtaq; Jaffery, Syed Husain Imran; Khan, Zarak (International journal of precision engineering and manufacturing, 2025)
This paper presents the machinability performance of uncoated, single-coated, and multicoated carbide tools during turning of Grade 5 (Ti6Al4V) Titanium alloy, which is challenging to machine due to its distinctive material properties. Coated tools with single-coated Titanium Aluminium Nitride (TiAlN) and multi-coated layer of Titanium Aluminium Nitride with Aluminium Chromium Nitride (TiAlN + AlCrN) coated inserts were utilized to assess surface roughness (Ra), tool wear rate (R), and chip morphologies under various cutting conditions using dry machining. Analysis of the used tools revealed that coated tools exhibited improved tool life and surface quality compared to uncoated tools across all cutting conditions. Multi-coated tools of TiAlN + AlCrN demonstrated a tool life increase of up to 15% compared to uncoated and single-coated tools, with surface roughness improvements ranging from 30 to 45% depending on cutting speed. Chip morphology analysis indicated an increase in the chip reduction coefficient with higher cutting speeds for all tool types. Coated tools exhibited the lowest chip-reduction coefficient due to the presence of TiAlN and AlCrN coatings, which control the tool chip contact length. Conversely, uncoated chip morphology resulted in larger chip thickness values compared to coated tools, particularly at cutting speeds above 100 m/min, attributed to poor heat dissipation and chemical reactions at the tool chip interface. Energy dispersive X-ray scanning electron microscopy (SEM/EDXS) analysis of worn uncoated inserts revealed a higher tendency towards Titanium adhesion compared to coated tools. The proposed multi-layer coatings of (TiAlN + AlCrN) used for dry machining proved highly beneficial for achieving economic machining objectives and may reduce the need for lubrication when processing Ti6Al4V alloys.